Other profitable activities on family agricultural holdings according to their economic size - Jonel Subić; Marko Jeločnik; Marijana Jovanović; Velibor Potrebić (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In the paper will be emphasized the importance of the other profitable activities (OPA) on the family agricultural holdings, according to their economic size within the territory of Republic of Serbia, with special focus on the Vojvodina Region. Economic size of the agricultural holding is recognized by the value of its total standard output (SA). Other profitable activities related to the agricultural holdings include incomes from agricultural products sale, rural tourism, fishery, etc., whether they are performed on or outside the holding. Other profitable activities that are not related to agricultural holdings include activities that do not consume resources of the holding, but only the labor, as like in previous case they may be carried on, or outside the holding. According to gained results, average economic size of the holding in the Republic of Serbia is 5.939 EUR, while the realized economic value on the family agricultural holdings (FAH) is 4.990 EUR. Census of Agriculture in 2012 showed that the highest average economic size of the agricultural holdings has a Vojvodina Region (12.032 EUR), what is 3,5 times higher than the value achieved in other regions. From the total sum of 631.552 agricultural holdings in the Republic of Serbia (family agricultural holdings (FAH), as well as legal entities (LE) and entrepreneurs) only 78.301 holdings possess DPA that are in relation to the holding (where 21% of them are within the economic class in range of 4.000 - 7.000 EUR). At the level of the Vojvodina Region, in total there were registered 147.624 agricultural holdings (AH), where 8.405 of them have OPA in relation to the holding (13,6% are within the class of economic sizes 100.000 and more EUR).
Keywords: 330; other profitable activities; family agricultural holdings; Vojvodina Region; Republic of Serbia